Nurse staffing and deficiency of care for inappropriate psychotropic medication use in nursing home residents with dementia. Issue 6 (7th April 2022) - Yoon, Jung Min; Trinkoff, Alison M.; Galik, Elizabeth; Storr, Carla L.; Lerner, Nancy B.; Brandt, Nicole; Zhu, Shijun
Abstract: Purpose: Psychotropic medications are used to manage behavioral symptoms of dementia in nursing homes despite limited efficacy and the risk of adverse effects, and may be considered an easier solution for the treatment of behavioral symptoms. However, non‐pharmacologic interventions are preferable but are most effective with consistent staffing. To address this, the Centers for Medicare and Medicaid Services implemented additional regulatory scrutiny through F‐tag for deficiencies of care, targeting inappropriate psychotropic medication use (F‐758 tag). The purpose of this study was to examine associations between nurse staffing levels and the occurrence of deficiency citations for inappropriate psychotropic medication use in residents with dementia symptoms. Design: This was secondary data analysis of a cross‐sectional study using CASPER (Certification and Survey Provider Enhanced Reporting) and PBJ (Payroll‐Based Journal) data from 14, 548 Medicare or Medicaid‐certified facilities surveyed between December 1, 2017 and December 31, 2018. Methods: Staffing measures included nursing hours per resident day and registered nurse skill‐mix. Generalized linear mixed models with facilities nested within states, were used to estimate the magnitude of the associations between the occurrence of inappropriate psychotropics use deficiency citations and nurse staffing levels. Covariates included facility location, size, ownership, the presence of dementia special care units, and the proportion of residents with dementia, depression, psychiatric disorders, mental behavioral symptoms, and residents with Medicare/Medicaid. Results: There were 1875 facilities with deficiency citations regarding inappropriate psychotropics use for residents with dementia. When controlling for covariates, facilities with greater hours per resident day for registered nurses (odds ratio [OR] = 0.54, 95% confidence interval [CI] = 0.44–0.67), certified nursing assistants (OR = 0.87, 95% CI = 0.77–0.99) and total nurse staff (OR = 0.87, 95% CI = 0.79–0.96) had significantly lower odds of inappropriate psychotropics use deficiency citations. Nursing homes with greater registered nurse skill‐mix had significantly lower odds of receiving the deficiency tags (OR = 0.10, 95% CI = 0.04–0.26). Conclusion: Citations for inappropriate psychotropic medication use among residents with dementia were less likely to occur in facilities with higher staffing levels for registered nurses, certified nursing assistants, total nurse staff, and greater registered nurse skill‐mix. Facilities need to be equipped with adequate nurse staffing levels to facilitate the use of non‐pharmacological interventions and reduce inappropriate psychotropic medication use. Clinical Relevance: Adequate nursing staffing is associated with fewer deficiencies related to the use of psychotropic medications to treat behavioral symptoms. Nursing home administrators and policymakers need to focus on assuring adequate nurse staffing levels to provide safe and high‐quality dementia care.